Mobile Carbapenemase Genes in Pseudomonas aeruginosa - Yoon, Eun-Jeong; Jeong, Seok Hoon (Frontiers in Microbiology, 2021)
Carbapenem-resistant Pseudomonas aeruginosa is one of the major concerns in clinical settings impelling a great challenge to antimicrobial therapy for patients with infections caused by the pathogen. While membrane permeability, together with derepression of the intrinsic beta-lactamase gene, is the global prevailing mechanism of carbapenem resistance in P. aeruginosa, the acquired genes for carbapenemases need a special attention, because horizontal gene transfer through mobile genetic elements, such as integrons, transposons, plasmids, and integrative and conjugative elements, could accelerate dissemination of the carbapenem-resistant P. aeruginosa. This review aims to illustrate epidemiologically the carbapenem resistance in P. aeruginosa, including the resistance rates worldwide and the carbapenemase-encoding genes along with the mobile genetic elements responsible for the horizontal dissemination of the drug resistance determinants. Moreover, the modular mobile elements including the carbapenemase-encoding gene, also known as the P. aeruginosa resistance islands, are scrutinized mostly for their structures.